Social-spatial segregation concepts, processes and outcomes - Lloyd, Christopher ca. 20./21. Jh; Wong, David W. S. ca. 20./21. Jh; Shuttleworth, Ian 1963- (The Policy Press, 2014)
This edited volume, bringing together leading researchers from the United States, the United Kingdom and Europe, offers a new approach to conceptualising segregation